2020
DOI: 10.1111/jdv.16808
|View full text |Cite
|
Sign up to set email alerts
|

STIs and the COVID‐19 pandemic: the lockdown does not stop sexual infections

Abstract: same pathogenic pathway and some clinical manifestations, including chilblains and retinal vasculopathy. In addition, this type I IFN response produces microvascular injury, 6 which has already been reported to be related to COVID-19 infection, and it could explain both chilblains and retinal vasculitis. Also, Kawasaki disease can share some similarities with COVID-19 infection. Both cause acral skin lesions, vasculitis and show increased serum interleukin 6 (IL-6) related to the immune response to the disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 8 publications
(8 reference statements)
2
29
0
4
Order By: Relevance
“…We read with great interest Balestri et al's report, 1 which showed that the incidence of sexually transmitted infection (STI) in the lockdown period between 9 March and 4 May 2020 during the COVID-19 pandemic was comparable to that during the same period in 2019. This observation suggested that infection control and policy, such as quarantine, social distancing and the closure of leisure venues, did not provide additional benefit regarding STI prevention.…”
Section: Editormentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest Balestri et al's report, 1 which showed that the incidence of sexually transmitted infection (STI) in the lockdown period between 9 March and 4 May 2020 during the COVID-19 pandemic was comparable to that during the same period in 2019. This observation suggested that infection control and policy, such as quarantine, social distancing and the closure of leisure venues, did not provide additional benefit regarding STI prevention.…”
Section: Editormentioning
confidence: 99%
“…Editor, Most data on cutaneous manifestations of COVID-19 rely on the evaluation of hospitalized patients. 1,2 Conversely, as COVID-19 requires social isolation, many low-symptomatic individuals develop dermatologic manifestations which prevalence is underestimated. 3 The prevalence of skin lesions was 20% among 88 Italian hospitalized patients.…”
Section: Self-reported Cutaneous Manifestations In 1429 Brazilian Covmentioning
confidence: 99%
“…Data from Madrid and Rome suggest a strong decrease in STDs and a syphilis diagnosis during the lockdown, as a result of social isolation and closure of leisure venues which has reduced the opportunity for casual sexual encounters. 4 , 5 In northern Italy, the area most affected by the Covid-19 pandemic, the incidence of STDs, including syphilis, seems comparable with the number of patients diagnosed before the lockdown, 6 while in Bologna the percentage of visits for syphilis, gonococcal pharyngitis, and inflammatory genital diseases had significantly increased, suggesting that the lockdown had not actually interfered with sexual activity..…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 The few available surveys dealing with this topic found a decreased incidence in all STD during the lockdown, 4 , 5 while other reports indicated no significant change. 6 , 7 Even less data are available specifically for syphilis. 4 For these reasons, we have performed a retrospective observational study of all patients newly diagnosed at the STDs Service of the Dermatology Clinic at Cagliari, part of the Italian sentinel surveillance system, during the first 6 months of each year, from 2016 to 2020.…”
Section: Introductionmentioning
confidence: 99%
“…2 At least theoretically, lockdown could lead to behavioural changes and a reduction in the risk of STIs. To date, published reports indicate that during the lockdown of Spring 2020, STI incidence was either comparable 3 or reduced 4 5 relative to previous years. Whether the apparent reduction indicates a true epidemiological change or rather an underestimation due to lack of presentation for diagnosis remains to be determined.…”
mentioning
confidence: 99%